2005
DOI: 10.1021/ie050128v
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Nitrogen, Oxygen, and Argon in Mono-, Di-, and Trivalent Cation-Exchanged Zeolite Mordenite

Abstract: Adsorption of nitrogen, oxygen, and argon is studied in zeolite mordenite (Si/Al = 5.5) with mono-, di-, and trivalent Na+, Li+, K+, Cs+, Ca2+, Sr2+, Ba2+, La3+, and Ce3+ as extraframework cations. Adsorption capacity, selectivity, and heat of adsorption show a strong dependence on the nature as well as the extent of the extraframework cations. The cation-exchanged mordenite samples show adsorption selectivity toward nitrogen from its mixture with oxygen or argon. The electrostatic interaction between adsorbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
(21 reference statements)
1
26
3
Order By: Relevance
“…4A-B (b-f), it is clearly indicated that the adsorption capacity of nitrogen in highly cation exchanged Ag x Li 96-x -LSX decreases sharply with an increase in the size of cations that agrees well with the literature. 31 In the case of lithium cations, the curve shows highest nitrogen adsorption capacity with small cation size. Yang et al reported, 10 the ionic radius of Ag + is (1.26 Å) considerably larger than that of Li + (0.68 Å).…”
Section: Influence Of Silver Ion Exchangementioning
confidence: 96%
See 1 more Smart Citation
“…4A-B (b-f), it is clearly indicated that the adsorption capacity of nitrogen in highly cation exchanged Ag x Li 96-x -LSX decreases sharply with an increase in the size of cations that agrees well with the literature. 31 In the case of lithium cations, the curve shows highest nitrogen adsorption capacity with small cation size. Yang et al reported, 10 the ionic radius of Ag + is (1.26 Å) considerably larger than that of Li + (0.68 Å).…”
Section: Influence Of Silver Ion Exchangementioning
confidence: 96%
“…However, the strong bonds between N 2 and Ag + cannot only be attributed to the ion-quadrupole interaction, but also relatively slow desorption and high heats of adsorption involves weak π-complexation bonds that play an important role in the reduction of N 2 adsorption and confirmed in the literature. 10,31 On the basis of these observations, it is therefore inferred here that near fully exchanged Ag x Li 96 -x -LSX zeolites as compared to their Li x Na 96-x -LSX zeolite analogs are not favorable for use in adsorption-based separations, not only because of the low N 2 adsorption capacity and N 2 /O 2 selectivity, but also have strong affinity for N 2 at low pressures that can easily create a low-pressure high "knee" in the adsorption isotherm, which results in difficulty of N 2 desorption for the purpose of adsorbent regeneration as shown in Figs. 4A-B (b-f) and found in good agreement with the literature.…”
Section: Influence Of Silver Ion Exchangementioning
confidence: 99%
“…For example selectivities of various MOFs and other materials for different gas compounds have been investigated by comparing the equilibrium adsorption capacity at specific conditions (Li et al 2009;Pawar et al 2009). In cationexchanged zeolite mordenite and MOFs, selective properties have been quantified by taking the ratio of the Henry's constants or comparing the isosteric enthalpy of adsorption of each gas (Peter et al 2005;Liu et al 2008;Moellmer et al 2012). More sophisticated methods of measuring the selectivity of CH 4 adsorption over N 2 adsorption are also reported, for example breakthrough measurements, however these experiments are tailored to specific process conditions and require elaborate experimental apparatus beyond the scope of this study.…”
Section: Selectivitymentioning
confidence: 99%
“…(1)), the obtained value of first Virial coefficient (A) was further used for the calculation of Henry's constant with the help of Eq. (2) [34].…”
Section: Characterizationmentioning
confidence: 99%